Dose rate in the highest irradiation area of the rectum correlates with late rectal complications in patients treated with high-dose-rate computed tomography-based image-guided brachytherapy for cervical cancer - Isohashi, Fumiaki; Akino, Yuichi; Matsumoto, Yuri; Suzuki, Osamu; Seo, Yuji; Tamari, Keisuke; Sumida, Iori; Sawada, Kenjiro; Ueda, Yutaka; Kobayashi, Eiji; Tomimatsu, Takuji; Nakanishi, Erina; et al. (Journal of radiation research, 2021)
Abstract The purpose of this study was to evaluate the effect of dose rate to the rectum on late rectal complications in patients treated with computed tomography (CT)-based image-guided brachytherapy (IGBT) for cervical cancer. The subjects were 142 patients with cervical cancer who underwent Ir-192 high-dose-rate (HDR)-IGBT between March 2012 and January 2018. The dose rate to the rectum was calculated using in-house software. The minimum, mean and maximum effective dose rate (EDR) was calculated for voxels of the rectal volume covered by cumulative doses >D0.1cc, >D2cc, and > D5cc. The average EDR of three to four brachytherapy sessions was calculated (EDR for patients; EDRp). The total dose of the rectum was calculated as the biologically equivalent dose in 2-Gy fractions (EQD2). The associations between EDRp for D0.1cc, D2cc, and D5cc and the respective rectal EQD2 values with late rectal complications were then analyzed. The median follow-up period was 40 months. Patients with rectal complications of ≥Grade 1 received a significantly higher mean EDRp for D0.1cc–5cc and had a greater EQD2 for D0.1cc–5cc. Multivariate analysis was performed using the mean EDRp for D2cc, EQD2 for D2cc, heavy smoking and BMI. Of these four variables, mean EDRp for D2cc (HR = 3.38, p = 0.004) and EQD2 for D2cc (HR = 2.59, p = 0.045) emerged as independent predictors for late rectal complications. In conclusion, mean EDRp and EQD2 were associated with late rectal complications in patients treated with HDR CT-based IGBT for cervical cancer.